2021
DOI: 10.1038/s41598-021-93476-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of pachyvessels associated with polypoidal choroidal vasculopathy in chronic central serous chorioretinopathy

Abstract: To investigate the association between clinical features of chronic central serous chorioretinopathy (CSC) and subsequent development of polypoidal choroidal vasculopathy (PCV). Characteristics and treatment response of PCV secondary to CSC were described. This retrospective observational study included 18 patients with chronic CSC (18 eyes) with subsequent PCV and 36 controls (36 eyes) with chronic CSC without PCV development during follow-up. Clinical features were compared between the two groups. A logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Our results showed that IL-4 was significantly associated with the choroidal thickness and the presence of polypoidal lesions in eyes with PNV. This is consistent with reports that showed that the development of polypoidal lesions was closely associated with development of pachyvessels 47 . Collectively, the PNV diseases appeared to be associated with vascular remodeling including the development of polypoidal lesions.…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that IL-4 was significantly associated with the choroidal thickness and the presence of polypoidal lesions in eyes with PNV. This is consistent with reports that showed that the development of polypoidal lesions was closely associated with development of pachyvessels 47 . Collectively, the PNV diseases appeared to be associated with vascular remodeling including the development of polypoidal lesions.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous reports that showed that the development of polypoidal lesions was closely associated with development of pachyvessels. 44 Collectively, the PNV diseases appear to be associated with a vascular remodeling including the development of polypoidal lesions. In addition, the pachyvessels may also promote choroidal neovascularization.…”
Section: Discussionmentioning
confidence: 99%